RNA-mediated dimerization of the human deoxycytidine deaminase APOBEC3H influences enzyme activity and interaction with nucleic acids - Feng, Yuqing (J Mol Biol, 2018)
Human APOBEC3H is a single-stranded (ss)DNA deoxycytidine deaminase that inhibits replication of retroelements and HIV-1 in CD4+ T cells. When aberrantly expressed in lung or breast tissue APOBEC3H can contribute to cancer mutagenesis. These different activities are carried out by different haplotypes of APOBEC3H. Here we studied APOBEC3H haplotype II, which is able to restrict HIV-1 replication and retroelements. We determined how the dimerization mechanism, which is mediated by a double-stranded RNA molecule, influenced interactions with and activity on ssDNA. The data demonstrate that the cellular RNA bound by APOBEC3H does not completely inhibit enzyme activity, in contrast to other APOBEC family members. Despite degradation of the cellular RNA, an approximately 12 nt RNA remains bound to the enzyme, even in the presence of ssDNA. The RNA-mediated dimer is disrupted by mutating W115 on loop 7 or R175 and R176 on helix 6, but this also disrupts protein stability. In contrast, mutation of Y112 and Y113 on loop 7 also destabilizes RNA-mediated dimerization but results in a stable enzyme. Mutants unable to bind cellular RNA are unable to bind RNA oligonucleotides, oligomerize, deaminate ssDNA in vitro, but ssDNA binding is retained. Comparison of A3H wild type and Y112A/Y113A by fluorescence polarization, single molecule optical tweezer, and atomic force microscopy experiments demonstrates that RNA mediated dimerization alters the interactions of A3H with ssDNA and other RNA molecules. Altogether, the biochemical analysis demonstrates that RNA binding is integral to APOBEC3H function.